Comparison of Retinal Layer Thickness and Capillary Vessel Density in the Patients with Spontaneously Resolved Acute Central Serous Chorioretinopathy - Han, Kyu Jin (J Clin Med, 2020)
We investigate retinal layer thickness and capillary vessel density (VD) in the patients with central serous chorioretinopathy (CSC) who recovered spontaneously and evaluate the correlation between the changes in these values and visual outcomes using swept-source optical coherence tomography (SS-OCT) and OCT angiography (OCTA). This retrospective case–control study included 34 eyes of 34 patients with spontaneously resolved acute CSC. The changes in retinal layer thickness and capillary VD were examined using SS-OCT and OCTA after complete resolution of subretinal fluid (SRF). The fellow eyes and 34 healthy eyes were used as controls. In the eyes with CSC, the outer retinal layer was significantly thinner than in the eyes of fellow and healthy controls. The foveal avascular zone area and VDs in the superficial and deep capillary plexus in the eyes with CSC were not significantly different from those in the eyes of fellow and healthy controls. The VD of the choriocapillaris in the eyes with CSC was significantly lower than that in the eyes of fellow and healthy controls. Correlation analyses revealed that the outer retinal layer thickness and initial visual acuity were positively correlated with the final visual acuity. Furthermore, the initial SRF area and height were negatively correlated with the outer retinal layer thickness after SRF resolution. Attenuation of outer retinal layer thickness and decreased VD of the choriocapillaris were observed in the eyes with spontaneously resolved acute CSC. The outer retinal layer thickness could be an important visual predictor of CSC.